Autonomous functions of structural domains on human tissue-type plasminogen activator. - van Zonneveld, A J (1986)
Transfected mouse Ltk- cells were employed for transient expression of recombinant human tissue-type plasminogen activator (t-PA; EC 3.4.21.31) or of recombinant-t-PA deletion proteins, encoded by SV40-pBR322-derived t-PA cDNA plasmids. The t-PA cDNA deletion mutants have two features in common, i.e., cDNA programming the signal peptide and the coding region for the light chain. Consequently, recombinant t-PA mutant proteins are efficiently secreted and display plasminogen activator activity. The gene encoding the amino-terminal heavy chain [an array of structural domains homologous to other plasma proteins (finger, epidermal growth factor, and kringle domains)] was mutated using restriction endonucleases to delete one or more structural domains. The stimulatory effect of fibrinogen fragments on the plasminogen activator activity of t-PA was demonstrated to be mediated by the kringle K2 domain and to a lesser extent by the finger/epidermal growth factor region but not by the kringle K1 domain. These data correlate well with the fibrin-binding properties of the recombinant t-PA deletion proteins, indicating that the stimulation of the activity by fibrinogen fragments is based on aligning the substrate plasminogen and t-PA on the fibrin matrix. Our results support the evolutionary concept of exon shuffling, arranging structural domains that constitute autonomous functions of the protein.